Methodological Reflection in a Pith Helmet - Babich, Nikolay (Journal of Economic Sociology, 2019)
This paper is a polemical response to the article “Criticism of the Interview Approach in Examining the Similarity of the Appearance of Products Belonging to the Same Product Category”, which also appeared in the Journal of Economic Sociology [2018, vol. 19, no 2, pp. 86–117]. In this work, Roman Bumagin and Dmitry Rogozin claim that in trademark similarity research, it is necessary to take into consideration the overall similarity of designs in the same product category. They also criticize the current research practices’ focus on survey methods and call for a fundamental revision of the decision-making process on trademark similarity. While welcoming the attention given to some important subjects (e.g., the need for controls and the background level of similarity), we question the appropriateness of Bumagin and Rogozin’s research procedure and draw attention to the instances of incorrect citations and the distortion of facts in their text. Using specific examples, we show that the arguments proposed in support of the criticism, in fact, illustrate the advantages of current research practices. The procedure actively uses experimental plans and considers the background level of similarity. Our article also asserts, more generally, that to criticize current decision-making in trademarks’ similarity from the perspective of scientism, as Bumagin and Rogozin have done, fails to reflect the specific conditions of arbitration (in a broad sense) authorities. Their goal is not only to establish the truth but also to resolve economic conflicts, and this requires not only a strict but an understandable research procedure. We conclude that hypercriticism in trademark similarity research causes a “colonial” attitude, and it prevents real research practice improvement.